Exploring the implementation of Whatsapp-assisted language learning of primary school in rural area - Weny Fitriana (Journal of English Language Teaching and Learning (JETLE), 2022)
The study aims to investigate the implementation of WhatsApp assisted language learning in rural area. This research involves descriptive qualitative research by using interview and observation that focuses on the use of Whatsapp in teaching vocabulary and involve sociocultural theory as the framework to analyze the implementation of this MALL application. Some reasons related to the preference of involving WhatsApp-assisted language teaching lies on the technical and pedagogical reason. The simplicity of using the application is the main reason in terms of technical one while the educational reasons involved the sense of belonging, flexible interaction, and autonomous learning. In term of assisting students to learn, the teacher take a role as a material provider, while the parents take more role that is scaffolding. However, the role of the teacher in scaffolding is not significant, therefore the next research may focus on the suitable activity that the teacher can apply on online teaching particularly for young children